ANALISIS SEMIOTIKA TENTANG PENCEGAHAN COVID 19 MELALUI KOMIK DIGITAL (STUDI PADA AKUN INSTAGRAM @MICECARTOON.CO.ID) - I Gede Titah Pratyaksa; Niluh Wiwik Eka Putri (UHN IGB Sugriwa Denpasar, 2022)
The socialization of Covid 19 Prevention by the government has still not been able to touch the basic layers of Indonesian society. This encourages efforts to spread awareness about 3M implementation, one of which is through persuasive communication through digital comics. The purpose of this study was to determine persuasive communication about the socialization of Covid 19 prevention through digital comics. This research uses a qualitative approach with a case study method on the Instagram @ micecartoon.co.id account. Data collection techniques using interviews, observation, and literature study. This research uses the concept of persuasive communication, socialization of Covid 19 prevention, and digital comics. The results of the study consisted of three things, namely the implementation of persuasive communication about the socialization of prevention of COvid 19 through digital comics which had an affective, cognitive, or conative objective. The strategy used is the strategy of composing messages, channel selection, and feedback. In addition, persuasive communication about the prevention of Covid 19 is also influenced by the visualization of comics as a medium through character depiction and color selection.